Strain Localization in the Root of Detachment Faults at a Melt‐Starved Mid‐Ocean Ridge: A Microstructural Study of Abyssal Peridotites From the Southwest Indian Ridge. (30th April 2021) - Bickert, M.; Cannat, M.; Tommasi, A.; Jammes, S.; Lavier, L.
Abstract: Detachment faults that exhume mantle peridotites to the seafloor play a major role in the accommodation of plate divergence at slow‐spreading ridges. Using 99 samples of partially serpentinized peridotites dredged from a nearly amagmatic segment of the eastern part of the Southwest Indian Ridge, we characterize the deformation processes active in the root zone of detachment fault systems. The deformation is heterogeneous even at the sample scale and combines both brittle and crystal‐plastic mechanisms. Strain localization is initially controlled by strength contrasts at the grain scale between olivine and orthopyroxene and between variably oriented olivine crystals. Orthopyroxene deformation is primarily brittle (microfractures), but kink bands and dynamic recrystallization are locally observed. In contrast, olivine deforms primarily by dislocation creep with dynamic recrystallization under high deviatoric stresses (80–270 MPa). Olivine grains poorly oriented to deform by dislocation glide display kink bands and localized microfractures. Dynamic recrystallization controlled by strain and stress concentrations produce anastomosing zones of grain size reduction (GSR). GSR zones contain limited late to post‐kinematic amphibole, suggesting the presence of small volumes of hydrous fluids. Plagioclase, when present, is post‐kinematic. This heterogeneous high‐stress deformation is observed, with variable intensity, in every sample investigated, suggesting that it was pervasively distributed in the root region of axial detachments. Abyssal peridotite samples from more magmatically robust slow mid‐ocean ridges do not show this pervasive high stress deformation microstructure, implying magma, when present, tends to localize most of the strain at the root of axial detachment systems. Key Points: Heterogeneous high stress deformation is observed in peridotites from the Eastern Southwest Indian ridge Stress and strain concentrations produce localized grain size reduction by dynamic recrystallization in olivine rich‐domains This deformation likely occurs at the root of axial detachment faults in magma‐starved mid‐ocean ridges